Inconsistency and social decision making in patients with Borderline Personality Disorder. (30th September 2016) - Preuss, Nora; Brändle, Laura S.; Hager, Oliver M.; Haynes, Melanie; Fischbacher, Urs; Hasler, Gregor
Abstract: Inconsistent social behavior is a core psychopathological feature of borderline personality disorder. The goal of the present study was to examine inconsistency in social decision-making using simple economic social experiments. We investigated the decisions of 17 female patients with BPD, 24 patients with major depressive disorder (MDD), and 36 healthy controls in three single shot economic experiments measuring trust, cooperation, and punishment. BPD severity was assessed using the Zanarini Rating Scale for BPD. Investments across identical one-shot trust and punishment games were significantly more inconsistent in BPD patients than in controls. Such inconsistencies were only found in the social risk conditions of the trust and punishment conditions but not in the non-social control conditions. MDD patients did not show such inconsistencies. Furthermore, social support was negatively correlated with inconsistent decision-making in the trust and punishment game, which underscores the clinical relevance of this finding. Highlights: Inconsistent behavior is a key feature of Borderline Personality Disorder (BPD). Behavioral inconsistency in BPD was investigated using economic exchange games. The results show that inconsistent behavior is also present in first encounters. Behavioral inconsistency negatively correlated with perceived social support.